Odpowiedzi

2010-03-14T19:01:23+01:00
A) A=(-7,5) B=(-4,-1)
5=-7a+b
-1=-4a+b

b=5+7a
-1=-4a+5+7a

3a=-6
a=-2
b=-9

y=-2x-9

b) A=(-2,6) B=(0,0)
6=-2a+b
0=0a+b

b=0
-2a=6
a=-3

y=-3x
Najlepsza Odpowiedź!
2010-03-14T19:05:33+01:00
A) A=(-7,5) B=(-4,-1)
5=-7a+b
-1=-4a+b




b=5+7a
-1=-4a+5+7a





3a=-6
a=-2
b=-9




y=-2x-9





b) A=(-2,6) B=(0,0)
6=-2a+b
0=0a+b




b=0
-2a=6
a=-3




y=-3x
2010-03-14T19:37:54+01:00
A)(x2-x1)(y-y1)=(y2-y1)(x-x1)
x2=-4 x1=-7 y1=5 y2=-1
(-4+7)(y-5)=(-1-5)(x+7)
3y-15=-6x-42
3y=-6x-27 /3
y=-2x-9
b)
x1=-2 x2=0 y1=6 y2=0
(0+2)(y-6)=(0-6)(x+2)
2y-12=-6x-12
2y=-6x /2
y=-3x